A Model Specification Test For GARCH(1, 1) Processes. (1st May 2015) - Leucht, Anne; Kreiss, Jens‐Peter; Neumann, Michael H.
Abstract: We provide a consistent specification test for generalized autoregressive conditional heteroscedastic (GARCH (1, 1)) models based on a test statistic of Cramér‐von Mises type. Because the limit distribution of the test statistic under the null hypothesis depends on unknown quantities in a complicated manner, we propose a model‐based (semiparametric) bootstrap method to approximate critical values of the test and to verify its asymptotic validity. Finally, we illuminate the finite sample behaviour of the test by some simulations.